Minor motion magnification based on spectral analysis. (October 2022) - Cao, Haibin; Du, Zhenlong; Li, Xiaoli; Chen, Dong
Abstract: Objects in the world are constantly in motion, and it is crucial for us to observe how they change. Although our visual system possesses significant levels of perception and interpretation of motion, it has limited sensitivity, the observer cannot perceive minor motions which are below the visual sensing threshold. Minor motion cannot readily be perceived via conventional methods. In this paper, a Euler motion amplification method based on the back projection of the derivative is proposed, in which the Riesz pyramid decomposition is applied for achieving a better hierarchical reconstruction. Compared to more traditional methods, the method proposed herein can hold much larger magnification, has lower time complexity, and is more resistant to noise. Experiments have demonstrated that the given algorithm achieves better minor magnification with the evaluation of the objective quantitative evaluation indicators.